1995
DOI: 10.1144/gsl.sp.1995.084.01.12
|View full text |Cite
|
Sign up to set email alerts
|

SAGA injection: a new combination IOR process for stratified reservoirs

Abstract: Specific features of North Sea sandstone reservoirs and reservoir fluids determine quite special conditions for water-alternating-gas (WAG) injection which must be taken into account when tuning WAG parameters for the particular stratification and anisotropy of a heterogeneous reservoir. Combining advantages of waterflooding and gas injection, WAG can be very effective in stratified reservoirs. Even so, gravity segregation and early breakthrough may cause poor sweep, especially in reservoirs with low restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The empirical model calculates foam mobility reduction factor and accounts for effects of various parameters, like, for example, critical surfactant concentration, capillary shear thinning, drying of foam, oil sensitivity and temperature on foam generation, stability and propagation in the reservoir (Cheng, et al 2000). Field experience showed successful FAWAG (Foam Assisted Water-Alternate-Gas) injection and successful application of simulation tools to predict foam behaviour (Cheng, et al 2000, Hanssen and Surguchev 1994, Hanssen, et al 1995, Skauge, et al 2002, Surguchev and Hanssen 1996.…”
Section: Mobility Control During Co 2 Injection Processesmentioning
confidence: 99%
“…The empirical model calculates foam mobility reduction factor and accounts for effects of various parameters, like, for example, critical surfactant concentration, capillary shear thinning, drying of foam, oil sensitivity and temperature on foam generation, stability and propagation in the reservoir (Cheng, et al 2000). Field experience showed successful FAWAG (Foam Assisted Water-Alternate-Gas) injection and successful application of simulation tools to predict foam behaviour (Cheng, et al 2000, Hanssen and Surguchev 1994, Hanssen, et al 1995, Skauge, et al 2002, Surguchev and Hanssen 1996.…”
Section: Mobility Control During Co 2 Injection Processesmentioning
confidence: 99%
“…Extensive reservoir evaluations showed that early gas breakthrough may be a potential problem. Application of foam for gas mobility control, fluid diversion, and blocking to reduce GOR in production wells was identified as attractive method to improve WAG performance [7][8]. Based on the promising results from the foam treatment studies it has been decided to evaluate a field pilot project.…”
Section: North Sea Fieid Pilotsmentioning
confidence: 99%
“…Production well foam treatment against gas cusp at the UK North Sea field was analyzed and pilot results discussed [6]. For injectant diversion, foam application by alternate injection of foamer and gas was found to offer a significant potential of improving WAG process efficiency in the other North Sea field (planned Norwegian North Sea pilot) [7,8,10]. Evaluation of these different foam processes allowed to identify the following critical foam parameters for field applications: gas mobility reduction factor, foam persistence, volume of foamer injected, foamer adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…4 Placement of a, surfactant slug and subsequent foam generation in the swept high permeable top layer was successfully demonstrated and gave efficient injectant diversion info the love permeable layers, resulting in complete sweep of the reservoir model by continued WAG . The proces, termed SAGA (Surfactant Alternating Gas Ameliorated) Injection, indicated significant potential of improved oil recovery by a suite of simplified reservoir simulations using a cross section from the Staffjord Formation .…”
Section: Introductionmentioning
confidence: 99%
“…The proces, termed SAGA (Surfactant Alternating Gas Ameliorated) Injection, indicated significant potential of improved oil recovery by a suite of simplified reservoir simulations using a cross section from the Staffjord Formation . 4 However, a large scale field test of SAG injection in the Snorre WAG pilot area witti interwell distances of 700-1500 meters has been considered to involve too high economic risk and be too time consuming witti respect to the necessary data recordmg, for a first step pilot. Therefore, to reduce the risk (cost and time) a production well test has been recommended (small amounts of surfactants are required compared to an injector treatment).…”
Section: Introductionmentioning
confidence: 99%